1995
DOI: 10.2355/isijinternational.35.250
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Equilibrium between BaO-BaF2-MnO Fluxes and Ferro-manganese Melts.

Abstract: Theequilibrium distribution ratio of manganese between BaO-BaF=-MnO slag and Mn

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Liu et al found that the increase in BaF 2 content in the BaO‐BaF 2 ‐MnO slag enhances the activity coefficient of MnO in the melts. They also mentioned that the CaF 2 in the BaO‐MnO slag is partly transformed to BaF 2 in the slag according to the following reaction:false(italicCaF2false)+false(BaOfalse)=false(CaOfalse)+false(italicBaF2false)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al found that the increase in BaF 2 content in the BaO‐BaF 2 ‐MnO slag enhances the activity coefficient of MnO in the melts. They also mentioned that the CaF 2 in the BaO‐MnO slag is partly transformed to BaF 2 in the slag according to the following reaction:false(italicCaF2false)+false(BaOfalse)=false(CaOfalse)+false(italicBaF2false)…”
Section: Resultsmentioning
confidence: 99%
“…BaCO 3 (or BaO) has been proposed as a fluxing additive for producing ultra‐low phosphorus ferromanganese alloys under oxidizing conditions because BaO‐based fluxes have relatively higher phosphate capacity than conventional CaO‐based fluxes . BaO‐ and MnO‐containing slags could be produced when BaO‐based fluxes are added during the dephosphorization reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The data on the distribution of manganese between the slag and metal have also been accumulated. 4,6,[8][9][10][11][20][21][22][23][24][25][34][35][36][37][38][39][40][41] In existing studies on MnO-containing slag system with ternary and above-components, the Al 2 O 3 -containing slag system was most heavily studied while the FeO-containing slag system was least studied. However, MnO-containing slag systems without Al 2 O 3 was found in studies that the MnO content in a FeO-containing slag system without P 2 O 5 was lower than 21 wt%, and in a slag system containing both FeO and P 2 O 5 , the MnO content was lower than 28 wt%.…”
Section: Thermodynamic Activity Of Mno In Cao-sio 2 -Mno-feo-mgo Molten Slagsmentioning
confidence: 99%
“…(36), which can be calculated from Eq. (38). The activity coefficients of FeO in each slag sample of the experimental slags are listed in Table 1.…”
Section: Activity Coefficient Of Feomentioning
confidence: 99%
“…[2][3][4][5][6] Several investigations had been carried out about the oxidizing de-P of ferromanganese with slags containing BaO. [7][8][9][10][11][12][13] However, the conventional oxidizing dephosphorization (de-P) is not feasible for manganese ferroalloys, especially for silicomanganese ferroalloys, due to the inevitable prior oxidation of manganese and silicon. Thus, reducing de-P should be applied for manganese ferroalloys using alkaline earth metals or their compounds, [14][15][16][17][18][19] for example, Ca-Si alloy.…”
Section: Introductionmentioning
confidence: 99%